2010
DOI: 10.1055/s-0030-1250159
|View full text |Cite
|
Sign up to set email alerts
|

Comparative X‐Ray and Conformational Analysis of a New Crystal of 13α,21-Dihydroeurycomanone with Eurycomanone fromEurycoma longifoliaand Their Anti-Estrogenic Activity Using the Uterotrophic Assay

Abstract: 13 α,21-Dihydroeurycomanone (1), a known quassinoid of Eurycoma longifolia Jack was recrystallized from chloroform into a novel crystal structure in space group P2 (1). Its X-ray data were compared with those of eurycomanone ( 2). Following intraperioneal injections at similar doses of 2.44 µmol/kg/day for 3 consecutive days, 2 displayed comparable potency with tamoxifen but was more potent than 1 in the anti-estrogenic effect against 17 α-ethynylestradiol (EE)-induced uterotrophy of immature rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The known constituents were identified as eurycomalactone ( 2 ), 19 7α-hydroxyeurycomalactone ( 3 ), 20 5,6-dehydroeurycomalactone ( 4 ), 4 eurycolactone E ( 5 ), 21 longilactone ( 6 ), 22 14,15β-dihydroklaieanone ( 7 ), 23 11-dehydroklaieanone ( 8 ), 24 eurycomanone ( 9 ), 22,25,26 13,21-dehydroeurycomanone ( 10 ), 22 laurycolactone A ( 11 ), 5 laurycolactone B ( 12 ), 5 1-methoxycarbonyl-β-carboline ( 13 ), 27 9-hydroxycanthin-6-one ( 14 ), 28 9-methoxycanthin-6-one ( 15 ), 28 9,10-dimethoxycanthin-6-one ( 16 ), 9 5-methoxy-4-hydroxycanthin-6-one ( 17 ), 29 canthin-6-one 9- O -β- d -glucoside ( 18 ), 30 scopoletin ( 19 ), 31 fraxidin ( 20 ), 31 eurylene ( 21 ), 12 pedunculoside ( 22 ), 32 vanillic acid ( 23 ), vanillic aldehyde ( 24 ), syringic acid ( 25 ), 1,1′-biphenyl-3,3′-dicarboxylic acid ( 26 ), isoaloeresin D ( 27 ), 33 and 3,5,6,7,8,3′,4′-heptamethoxyflavone ( 28 ). 34 Compound identification was carried out by means of mass spectrometry and NMR spectroscopy as well as by comparison of physical and spectroscopic data with those of reference compounds reported in the literature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The known constituents were identified as eurycomalactone ( 2 ), 19 7α-hydroxyeurycomalactone ( 3 ), 20 5,6-dehydroeurycomalactone ( 4 ), 4 eurycolactone E ( 5 ), 21 longilactone ( 6 ), 22 14,15β-dihydroklaieanone ( 7 ), 23 11-dehydroklaieanone ( 8 ), 24 eurycomanone ( 9 ), 22,25,26 13,21-dehydroeurycomanone ( 10 ), 22 laurycolactone A ( 11 ), 5 laurycolactone B ( 12 ), 5 1-methoxycarbonyl-β-carboline ( 13 ), 27 9-hydroxycanthin-6-one ( 14 ), 28 9-methoxycanthin-6-one ( 15 ), 28 9,10-dimethoxycanthin-6-one ( 16 ), 9 5-methoxy-4-hydroxycanthin-6-one ( 17 ), 29 canthin-6-one 9- O -β- d -glucoside ( 18 ), 30 scopoletin ( 19 ), 31 fraxidin ( 20 ), 31 eurylene ( 21 ), 12 pedunculoside ( 22 ), 32 vanillic acid ( 23 ), vanillic aldehyde ( 24 ), syringic acid ( 25 ), 1,1′-biphenyl-3,3′-dicarboxylic acid ( 26 ), isoaloeresin D ( 27 ), 33 and 3,5,6,7,8,3′,4′-heptamethoxyflavone ( 28 ). 34 Compound identification was carried out by means of mass spectrometry and NMR spectroscopy as well as by comparison of physical and spectroscopic data with those of reference compounds reported in the literature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The eurycomanone ( 1 ; Purity > 96%), eurycomanol ( 2 ; Purity > 95%), 13α,21‐dihydroeurycomanone ( 3 ; Purity > 95%) and 13α(21)‐epoxyeurycomanone ( 4 ; Purity > 95%) (Fig. ) were isolated and purified following the protocol described previously (Teh et al ., , , ). The purity of the compounds was determined with Empower 2 workstation software (Waters, Milford, MA, USA) operated in a Waters Delta Prep HPLC system equipped with a Waters 2996 photodiode array detector.…”
Section: Methodsmentioning
confidence: 99%
“…The eurycomanone (1; Purity > 96%), eurycomanol (2; Purity > 95%), 13α,21dihydroeurycomanone (3; Purity > 95%) and 13α(21)epoxyeurycomanone (4; Purity > 95%) ( Fig. 1) were isolated and purified following the protocol described previously (Teh et al, 2010(Teh et al, , 2011a(Teh et al, , 2011b 13 C NMR (C 5 D 5 N, 175 MHz): 10.9 (C-19), 23 (C-18), 26.2 (C-6), 42.7 (C-5), 46.5 (C-10), 48.3 (C-9), 53.1 (C-8), 68.2 (C-20), 72.3 (C-15), 76.4 (C-7), 79.9 (C-14), 81.5 (C-12), 85 (C-1), 110.1 (C-11), 119.9 (C-21), 126.6 (C-3), 148.5 (C-13), 163.1 (C-4), 174.4 (C-16), 198 (C-2). Analysis of chemical content in E. longifolia extract by HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…Eurycomanone is the major quassinoid found in E. longifolia extracts, and it is supposed to be primarily responsible for the pharmacological or biological activities of E. longifolia , as mentioned earlier (Chan, Choo, Morita, & Itokawa, ; Chua et al, ; Han, Kim, Rehman, Choe, & Yoo, ; Han, Jang, Kim, Kim, & Yoo, ; Low, Choi, Wahab, Das, & Chan, ; Low et al, ; Miyake, Tezuka, Awale, Li, & Kadota, ; Teh et al, ; Wong et al, ; Zakaria, Rahmat, Pihie, Abdullah, & Houghton, ). It has been reported that the content of eurycomanone in E. longifolia root extracts reaches 9.95% (Han et al, , ; Teh, Murugaiyah, & Chan, ).…”
Section: Introductionmentioning
confidence: 82%